Respuesta :

Answer:

x= -6

Step-by-step explanation:

2(x-4)-3(2x+2)=2(x+11)

multiply numbers in parenthesis by 2 and multiply numbers in parenthesis by -3 and multiply parenthesis by 2.

2x-8-6x-6=2x+22

subtract 2x to 2x

-8-6x-6=22

subtract -8 to -6 but since there both negatives the equation is addition.

-14-6x=22

move constant to the right and change -14 as a positive.

-6x=22+14

add 22 to 14

-6x=36

divide both sides by -6

x= -6

2(x-4)-3(2x+2)=2(x+11)
2x-8-6x-6=2x+22
-4x-14=2x+22
-6x=36
x=-6
ACCESS MORE